Analyzing human behavior in cyberspace - Yan, Zheng 1958- (A volume in the Advances in human and social aspects of technology (AHSAT) book series, 2019)
"This book explores new ideas and research findings related to psychological aspects and serves as a vehicle for promoting techniques and methodologies derived from rigorous research and practices that use psychological and cognitive principles to design and develop cyber learning"...